Answer:
The equation of the line is 3 x - 4 y + 22 = 0.
Step-by-step explanation:
Here the given points are (-6, 1) & (-2, 4)
Equation of a line whose points are given such that
( [tex]x_{1}, y_{1}[/tex]) & ( [tex]x_{2}, y_{2}[/tex] )-
y - [tex]y_{1}[/tex] = [tex]\frac{y_{2} - y_{1} }{x_{2} - x_{1} }[/tex] ( x - [tex]x_{1}[/tex] )
i.e. y - 1 = [tex]\frac{4-1}{-2 - (-6)}[/tex] ( x- (-6))
y - 1 = [tex]\frac{4-1}{-2 + 6}[/tex] ( x + 6 )
y - 1 = [tex]\frac{3}{4}[/tex] ( x + 6 )
4 ( y - 1 ) = 3 ( x + 6)
4 y - 4 = 3 x + 18
3 x - 4 y + 22 = 0
Hence the equation of the required line whose passes trough the points ( -6, 1) & ( -2, 4) is 3 x - 4 y + 22 = 0.